Answer:
18h - 3hk
Step-by-step explanation:
3h(6 - k)
= 3h(6) + 3h(-k)
= 18h + -3hk
= <u>18h - 3hk</u>
It really depends on your preference of method
Answer:
500,000
Step-by-step explanation:
Font know hope you figure it out
-9x-6y=15
9x-10y=145
Find y first by eliminating the x.
Add the two equations together.
-9x+9x-6y+-10y=15+145
-6y+-10y=15+145
-6y-10y=160
-16y=160
divide both sides by -16 to get +y
-16y/-16=160/-16
y=-10
Use the substitution method to find x
-9x-6y=15
-9x-6(-10)=15
Do the bracket first
-9x+60=15
Move +60 to the other side. Sign changes from +60 to -60.
-9x+60-60=15-60
-9x=-45
Divide both sides by -9
-9x/-9=-45/-9
x=5
Answer:
( 5,-10)